SYSTEMATIC REVIEW: EFFECTIVENESS OF POINT-OF-CARE TESTING IN RAPID DIAGNOSIS OF CARDIAC EMERGENCIES - Areeba Ali Khan; Murk; Kashish; Rida Fatima Syed; Simran; Mohammed Ali Yassin Malallah; Khawla Aljasmi; Zeyad Essam Eid; Mariam Islam Ali; Abdullah Aliyan (Journal of Population Therapeutics and Clinical Pharmacology, 2025)
Background: Accurate diagnosis for cardiac emergencies, such as acute coronary syndrome (ACS) and Myocardial infarction (MI) through quick identification is essential for preventing complications that can lead to fatalities. However, the ordinary laboratory methods can lead to delayed diagnosis which can be detrimental for patient health outcomes. Therefore, emergency medical centers have adopted point-of-care testing (POCT) as a direct biomarker analysis modality, rendering real-time biomarker results for immediate decision-making needs. The scientific studies scrutinize Point-of-care testing (POCT) for diagnostic accuracy, improving healthcare efficiency and reducing diagnostic delays. Objectives: The systematic review represents the efficacy of point-of care testing by number of methods which includes diagnostic precision, streamlining the treatment timeline , patient health outcomes and accelerating the operating systems. The review also highlights the shortcomings and the opportunities associated with the implementation of PCOT. Methodology: The research evaluated the three peer- reviewed databases such as PUbMed, Scopus and Google Scholar. The research for the PCOT implementation in cardiac emergencies were included and then published between 2021 and 2024. A total of 27 articles have been utilized to incur the desired results which included, diagnostic specificity, speedy testing, patient outcomes and clinical making decisions. An analysis of the collected research yielded essential results about how POCT tests as compared to traditional laboratory methods. Results: According to the review results POCT produces rapid diagnostic results which become available within minutes thus excelling the traditional laboratory diagnosis methods. The quick results delivered through POCT allows medical professionals to perform life-saving treatments, mitigating emergency department (ED) delays thus streamlining patient hospital flow. Cardiac biomarker detection through POCT offers both high discrimination power and detection accuracy especially the ability of the identify troponin markers that works effectively. Studies prove that the implementation of Point of Care Testing (POCT) within emergency scenarios leads to reduced admission of patients to hospitals and better usage of healthcare resources. The implementation of POCT faces various constraints because results differ from test to test and poses regulatory challenges and costs more per examination. Nevertheless, the combination of artificial intelligence-assisted point-of-care testing and multiplexed biomarker detection technologies have rendered accurate diagnostic outcomes through innovations. Conclusion: The rapid diagnosis of cardiac emergencies should be revolutionized through Point of Care Testing because it provides accelerated diagnoses together with optimized clinical workflow management. However, the implementation of Point-of-Care Testing faces a number of challenges: accuracy-based difficulties, financial constraints and technical installation hindrance. Although these challenges can be reduced by the implementation standardized procedures together with technological innovation in point-of-care testing. Researchers need to conduct extensive clinical tests while developing automated diagnostic systems for enhancing the accuracy and accessibility of point-of-care tests within healthcare organizations.